CAN PRODUCT LEADERSHIP BE A PREDICTOR OF A CUSTOMER’S LOYALTY? - MS. Eric Santosa (Journal of Indonesian Economy and Business (JIEB), 2014)
Leading companies commonly employ a particular strategy to cover a market. They might choose product leadership, service support excellence, customer intimacy strategy, as well as a combination of them. The use of these strategies is obviously to gain more customers, since the product becomes a choice as an effect of the brand equity strengthening. While firms are very concerned with customer loyalty to maintain a stable sales volume, a question arises whether the brand equity has an effect on the customer’s loyalty. Logically, if a strategy can develop the product’s brand equity which in turn propels cutomers to buy it, it will hopefully improve customers’ loyalty as well. Therefore, this study is designed to answer the questions, (1) which strategy (among the three) adds power to the brand equity, (2) the brand equity is influential to the customer’s loyalty, and (3) the product leadership can predict the customer’s loyalty. Three antecedents of brand equity are employed, i.e. product leadership, service support excellence, and customer intimacy. These three variables, along with brand equity can also indicate as predictors of customer’s loyalty. A sample consisting of 100 respondents withdrawn through a judgment method. Data were analyzed by Amos 5.0 and SPSS 16.0. The results denote that the relationships between product leadership and customer intimacy to brand equity, also brand equity to customer’s loyalty are significant. On the contrary, the relationship of service support excellence to brand equity and the relationship of product leadership to customer’s loyalty are trivial.